1943
DOI: 10.1021/ie50404a013
|View full text |Cite
|
Sign up to set email alerts
|

Nitrated Wood

Abstract: THE exact nature of the chemical components of wood and their relation to one another as they exist in the woody tissue is unknown. Wood is not a uniform mixture of cellulose, hemicelluloses, and lignin, since these substances are distributed in varying proportions in the different morphological parts of the tissue. Physical means of separating the cell wall components, such as extraction or solution and fractionation, are not possible. Chemical methods of isolating any of the constituents of wood are all dras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1944
1944
1981
1981

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Coppick and Jahn (56) in 1943 made a study of nitrated wood, and described a procedure for fractionating nitrated spruce mechanical pulp by slow precipitation from acetone with alcohol and water. Eight fractions were obtained.…”
Section: Fractional Precipitationmentioning
confidence: 99%
“…Coppick and Jahn (56) in 1943 made a study of nitrated wood, and described a procedure for fractionating nitrated spruce mechanical pulp by slow precipitation from acetone with alcohol and water. Eight fractions were obtained.…”
Section: Fractional Precipitationmentioning
confidence: 99%
“…of the accuracy of the measurement of the flow times of dilute high-polymer solutions in conjunction with suitable calibration or correction of the viscometer will provide viscosity data which will make possible a more critical evaluation of the several methods of extrapolation (6,7,9) for obtaining intrinsic viscosities.…”
Section: Improvementmentioning
confidence: 99%
“…The realization of this end is, of course, based on a proper appreciation of the variables involved (1,4,6,10,13) and the development of apparatus embodying the inferred degrees of precision in the measurement or control of these variables. An outstanding treatment of this problem has already been provided by Jones and Talley (8).…”
Section: Improvementmentioning
confidence: 99%
“…For these relatively small amounts it would appear that a colorimetric method might be satisfactory for routine work. Feigl (2) found that lead dioxide oxidized nickel in alkaline solution to a valence higher than 2, and that addition of dimethylglyoxime to this solution gave a red coloration rather than a precipitate. This procedure was improved by Rollet U), who used bromine water instead of lead dioxide, and this method has found many applications (I, S, 5).…”
Section: Manymentioning
confidence: 99%
“…The publication of the Staudinger (11, 12,13) empirical viscosity-molecular -weight relationship gave great impetus to the investigation of methods for the determination of the weightaverage molecular weights of high polymeric compounds. Coppick (2) has recently reviewed and discussed the more significant papers that have been published relating the viscosity of solutions of high polymers with the degree of polymerization. The procedure most widely used is to relate viscosity data obtained at relatively high concentrations with the value of the viscosity function at infinite dilution through the use of mathematical equations (2, 4, 5, 6, 8, 14).…”
mentioning
confidence: 99%